The building of the educational course «the theory of graphs» for the bachelors of the mathematical department - Irina V. Sukhan (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2017)
The Disciplines, which deal with the discrete mathematics, contribute to the formation the competencies among the students- bachelors of mathematical department, which the Educational Standart requires. This article deals with the different variants of building the work program of one of the parts of the discrete mathematics - the theory of graphs. For the optimal variant the author offers the spiral variant of building the work program, which allows to turn back many times for the studied concepts on the qualitatively new level.